Enhanced Production of Bioethanol by Fermentation of Autohydrolyzed and C4mimOAc-Treated Sugarcane Bagasse Employing Various Yeast Strains - Muzna Hashmi; Aamer Ali Shah; Abdul Hameed; Arthur J. Ragauskas (Energies, 2017)
This study examines the fermentation of autohydrolyzed and 1-n-butyl-3-methylimidazolium acetate (C4mimOAc) pretreated sugarcane bagasse, using four different yeast strains to determine the efficiency of bioethanol production. Three strains of Saccharomyces cerevisiae (S. cerevisiae) and one of Scheffersomyces stipitis (S. stipitis) were employed in this study. It was observed that the sugarcane bagasse autohydrolyzed at 205 °C for 6 min with subsequent enzymatic hydrolysis exhibited the maximum ethanol yield of 70.92 ± 0.09 mg/g-substrate when S. cerevisiae MZ-4 was used. However, a slightly higher ethanol yield of 78.78 ± 0.94 mg/g-substrate was obtained from C4mimOAc pretreated bagasse employing S. cerevisiae MZ-4. The study showed that the newly isolated MZ-4 strain exhibited better ethanol yield as compared to commercially available yeast strains S. cerevisiae Uvaferm-43, S. cerevisiae Lalvin EC-1118, and S. stipitis.